Disaster Preparedness Among University Students in Guangzhou, China: Assessment of Status and Demand for Disaster Education. (26th September 2016) - Tan, Yibing; Liao, Xiaolan; Su, Haihao; Li, Chun; Xiang, Jiagen; Dong, Zhaoyang
Abstract: Objective: This study had 2 aims. First, we evaluated the current levels of disaster preparedness among university students in southern China. Second, we assessed students' demands for future disaster education. In addition, we examined the influence of demographic factors on current disaster preparedness status and demand. Methods: A cross-sectional design was used. The data were collected from 1893 students in 10 universities in the Guangzhou Higher Education Mega (GHEM) center. A self-administered questionnaire developed for this study was administered to assess the current status and demand for disaster education. Results: The results are based on 1764 valid questionnaires. Among the participants, 77.8% reported having had disaster education experiences before, 85.5% indicated their desire for a systematic disaster course, and 75.4% expressed their willingness to take such a course upon its availability. The total mean score for demand for disaster course content (5-point Likert scale) was 4.17±0.84, with items relating to rescue skills given the highest scores. These results suggested that students had high desires for disaster preparedness knowledge, especially knowledge concerning rescue skills. We observed significant differences in disaster education experiences between male and female students and across programs, school years, and home locations. Furthermore, we observed significant differences in demand for disaster course content between male and female students and across universities, student programs, years of school, and students' majors. Conclusion: A systematic disaster course focused on rescue skills is needed by all types of universities. To improve the disaster education system in universities, disaster drills should be performed on a semester basis as a refresher and to enhance disaster preparedness. The government and universities should support building a simulated disaster rescue center and recruit faculty from the emergency department, especially those who have had disaster relief experience. ( Disaster Med Public Health Preparedness . 2017;11:310–317)